2015
DOI: 10.2471/blt.15.157818
|View full text |Cite
|
Sign up to set email alerts
|

Kangaroo mother care: a systematic review of barriers and enablers

Abstract: ObjectiveTo investigate factors influencing the adoption of kangaroo mother care in different contexts. MethodsWe searched PubMed, Embase, Scopus, Web of Science and the World Health Organization’s regional databases, for studies on “kangaroo mother care” or “kangaroo care” or “skin-to-skin care” from 1 January 1960 to 19 August 2015, without language restrictions. We included programmatic reports and hand-searched references of published reviews and articles. Two independent reviewers screened articles and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
253
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(273 citation statements)
references
References 101 publications
11
253
2
7
Order By: Relevance
“…The systematic review by Seidman et al 25 proposed that resource-related barriers (eg, lack of guidelines/education) and sociocultural barriers (eg, concerns about medical conditions/care) negatively affected nurses; our study supports these points. Furthermore, other studies also proposed that lack of knowledge and skills were main barriers to KC implementation,23 26–29 as well as medical staff reluctance to allow KC 10 28–30. Resistance of medical staff is mainly associated with fear of harming infants and lack of experience and specific education in KC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review by Seidman et al 25 proposed that resource-related barriers (eg, lack of guidelines/education) and sociocultural barriers (eg, concerns about medical conditions/care) negatively affected nurses; our study supports these points. Furthermore, other studies also proposed that lack of knowledge and skills were main barriers to KC implementation,23 26–29 as well as medical staff reluctance to allow KC 10 28–30. Resistance of medical staff is mainly associated with fear of harming infants and lack of experience and specific education in KC.…”
Section: Discussionmentioning
confidence: 99%
“…WHO reports an average preterm birth rate of 7.1% in China, which makes the country second to India in the highest number of preterm births (ie, >250 000 in 2010) 10. In 2016, Gregson  et al 11 reported that KC is not well known in China; however, with assistance from an international charity, UK midwives have helped promote KC in China.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, we continuously observed clinical care and KMC practice from the time of enrolment to discharge, up to a maximum of 14 days. In a recent systematic review, only 12% of included studies reported the duration of KMC [79]. For the acceptability sub-study, we interviewed 10 parents (8 mothers and 2 fathers) and 10 providers who had experienced a preterm birth or cared for preterm neonates, respectively.…”
Section: Limitationsmentioning
confidence: 99%
“…KMC for low birth weight newborns in community settings may greatly improve survival, especially where access to health facilities is limited. In low birth weight newborns (< 2000 g) who are clinically stable, kangaroo mother care reduces mortality and if widely applied could reduce deaths in preterm newborns (Chan et al 2016). Research from various countries also suggests that KMC is a cost-effective method for treating preterm infants, mothers who have practiced KMC may find it acceptable .…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of the evidence, country-level adoption and implementation of kangaroo mother care have been limited and global coverage remains low (Chan et al 2016).…”
Section: Introductionmentioning
confidence: 99%